PENGARUH LIKUIDITAS DAN EFISIENSI MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2016 - -, Endang Saraswati (EKONOMIA, 2018)
Financial Management is an important role in every company in managing and earn profits, especially in Pharmaceutical companies listed on the Indonesia Stock Exchange. The formulation of this research problem is, whether liquidity (current ratio) has a significant effect on profitability (return on investment) in pharmaceutical companies listed in Indonesia Stock Exchange (BEI) period 2014-2016, Is the working capital turnover significant profitability (return on investment) in pharmaceutical companies listed in Indonesia Stock Exchange (BEI) period 2014-2016, Whether the current ratio and working capital turnover significantly affect profitability (return on investment) in pharmaceutical companies which is listed in Indonesia Stock Exchange (BEI) period 2014-2016.Theoretical basis in this study is financial management that focuses on current ratio (CR), Working Capital Turnover (WCT) and Return On Investment (ROI). Analyzer used is doubled linear ratio and regression analysis.Based on the results of analysis and discussion on the pharmaceutical company in the perceived by the writer known liquidity variable (CR) has a positive and not significant impact on profitability (ROI), working capital efficiency (WCT) has a positive and significant impact on profitability (ROI), and both variables liquidity (CR) and working capital efficiency (WCT) together have a positive and significant impact on profitability (ROI).Based on the results of existing research, suggested for the next researcher is to add factors that affect profitability, increase the scope of research population not only pharmaceutical companies but in other sectors, add the observation period and increase the observation period of research so that the results obtained more accurate